Gallium-68 fibroblast activation protein inhibitor positron emission tomography in cardiovascular disease - Mpanya, Dineo; Sathekge, Mike; Klug, Eric; Damelin, Jenna; More, Stuart; Hadebe, Bawinile; Vorster, Mariza; Tsabedze, Nqoba (Frontiers in Nuclear Medicine, 2023)
Gallium-68 fibroblast activatingactivation protein inhibitor ([ 68 Ga]Ga-FAPI) is a new radiopharmaceutical positioning itself as the preferred agent in patients with malignant tumours, competing with 2-Deoxy-2-[18F]fluoro-d-glucose (2-[ 18 F]FDG) using positron emission tomography (PET). While imaging oncology patients with [ 68 Ga]Ga-FAPI PET, incidental uptake of [ 68 Ga]Ga-FAPI has been detected in the myocardium. This review summarises original research studies associating the visualisation of FAPI-based tracers in the myocardium with underlying active cardiovascular disease.